Analisis Perbaikan Faktor Daya Sistem 11 Bus Dengan Metode Optimal Capacitor Placement - Baginda Asyraq Nasution; Rafles Marulitua Situmorang; Arwadi Sinuraya; Desman Jonto Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Electric power distribution networks generally receive energy after passing through the transmission system and function to step down and deliver voltage to end consumers. Throughout this delivery process, distribution networks are vulnerable to various disturbances, one of which is voltage drop, which can degrade power quality and disrupt system operational stability. This study aims to address voltage drop issues in distribution networks by applying the Optimal Capacitor Placement (OCP) method. OCP is used to determine the optimal locations and capacities of capacitors to improve voltage profiles, reduce power losses, and enhance the power factor. The research approach includes single-phase distribution network modeling, numerical simulations of loads and operating conditions, and performance evaluation before and after capacitor installation. The analysis focuses on voltage parameters, power losses, power factor, and operational stability in critical network segments. The results show that optimal capacitor placement can stabilize voltage within operational standards, reduce voltage fluctuations, and improve energy distribution efficiency.